2021
DOI: 10.3390/dj9120145
|View full text |Cite
|
Sign up to set email alerts
|

Dental Trauma at a University Dental Clinic in Milan including the SARS-CoV-2 Period

Abstract: The aim of this study i.e., is to present the distribution of traumatic dental injuries (TDI) in 306 patients registered at the Unit of Dental Emergencies at a University Dental Clinic in Milan, Italy, between June 2019 and May 2021. This time frame includes the beginning of the SARS-CoV-2 pandemic. Information regarding age, gender, number and type of injured teeth, type of traumatic injury, and data on where or how the injury happened were recorded. Seventy-nine percent of patients can be classified as pedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…However, this comparison bet ween the t wo periods should be made cautiously, because the interval corresponding to the period prior to the pandemic, in most cases, extends for a greater number of months in the child's life than the period of social isolation (approximately 12 to 15 months after the beginning of the pandemic). A study by Pederielli et al, 10 conducted with individuals of all ages during the pandemic, showed a decrease in the frequency of TDI cases during the social isolation period, compared with the months before and after the pandemic. The authors suggested that the risk of TDI was reduced by indoor life during this period.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, this comparison bet ween the t wo periods should be made cautiously, because the interval corresponding to the period prior to the pandemic, in most cases, extends for a greater number of months in the child's life than the period of social isolation (approximately 12 to 15 months after the beginning of the pandemic). A study by Pederielli et al, 10 conducted with individuals of all ages during the pandemic, showed a decrease in the frequency of TDI cases during the social isolation period, compared with the months before and after the pandemic. The authors suggested that the risk of TDI was reduced by indoor life during this period.…”
Section: Discussionmentioning
confidence: 97%
“…The scientific community reports that the most frequent cause of a TDI is falling from a height. 8 Furthermore, since TDIs occur more often at or around the home, 9,10 children are at a higher risk of most traumatic accidents in this environment. Therefore, social isolation was unlikely to result in a decrease in the incidence of TDIs requiring treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the largest quarantine attempt in human history to prevent the transmission of an infectious respiratory disease. [ 10 ] Dental traumatology is a widespread public healthcare problem. It can be influenced by various factors, such as socioeconomic status or environment.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these injuries occur in the anterior teeth, and therefore cause phonetic and functional, as well as cosmetic problems. A recent report noted that the teeth most commonly affected by dental trauma were the upper central incisors 32) . Dental trauma can sometimes cause the tooth to lose its integrity, and it can also be partially or totally displaced from its anatomical position.…”
Section: Introductionmentioning
confidence: 99%